2022
DOI: 10.31940/ijaste.v6i1.65-71
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tourism Infrastructure Asset Quality on Tourist Satisfaction: A Case on Forest Tourism in Tasikmalaya Regency

Abstract: This study aims to determine the effect of the quality of tourism infrastructure assets on tourist satisfaction on forest tourism in Tasikmalaya Regency including the quality of accommodation, quality of accessibility and quality of amenities. The research population is tourists who have visited the Batu Hanoman Waterfall, Batu Blek Waterfall, Candung Waterfall, and Ciparay Waterfall in Tasikmalaya Regency with a sample size of 336 respondents, applying a purposive sample. The data is processed using the Struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This present study, on the other hand, integrates the variables of main facilities and supporting facilities of water parks in addition to attraction and accessibility. Besides, this study explores the young water park tourist segment; this differs from other previous studies which do not focus on such segment (Biswas et al, 2020;Chenini and Touaiti, 2018;Nguyen Viet et al, 2020;Sugiama et al, 2022Sugiama et al, , 2023. Therefore, this research aims to investigate (1) the direct effect of attraction to satisfaction and revisit intention, accessibility to satisfaction and revisit intention, main facility to satisfaction and revisit intention, support facility to revisit intention, satisfaction on revisit intention; and (2) the indirect effect of attraction on revisit intention through satisfaction, accessibility on revisit intention through satisfaction, main facility on revisit intention through satisfaction, and support facility on revisit intention through satisfaction.…”
Section: Introductionmentioning
confidence: 86%
“…This present study, on the other hand, integrates the variables of main facilities and supporting facilities of water parks in addition to attraction and accessibility. Besides, this study explores the young water park tourist segment; this differs from other previous studies which do not focus on such segment (Biswas et al, 2020;Chenini and Touaiti, 2018;Nguyen Viet et al, 2020;Sugiama et al, 2022Sugiama et al, , 2023. Therefore, this research aims to investigate (1) the direct effect of attraction to satisfaction and revisit intention, accessibility to satisfaction and revisit intention, main facility to satisfaction and revisit intention, support facility to revisit intention, satisfaction on revisit intention; and (2) the indirect effect of attraction on revisit intention through satisfaction, accessibility on revisit intention through satisfaction, main facility on revisit intention through satisfaction, and support facility on revisit intention through satisfaction.…”
Section: Introductionmentioning
confidence: 86%
“…The results of interviews with several local residents found that they tend to think that tourist objects have not been managed properly by providing a sense of security, beauty, comfort, cleanliness, fun, comfort, satisfaction, and so on to tourists. Even though all of these aspects greatly influence tourism development (Buana & Sunarta, 2015;Suharto, 2016;Fanani & Pangestuti, 2017;Ćurčić et al, 2021;Sugiama, Oktavia & Karlina, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The desire to achieve good results from the development of a Tourism Village requires good planning, goals and targets, adequate infrastructure, good marketing, and availability and absorption of manpower. The development of the potential of a tourism village must have clear objectives and concrete targets to be achieved (Fitari & Ma'rif, 2017;Junaid, 2020;Lòpez-Sanz et al, 2021;Abdo, 2021) and supported by infrastructure in the form of adequate physical facilities and infrastructure such as clean water supply, energy sources, waste handling, transportation and other services (Almeida & Machado, 2021;Sugiama, Oktavia, & Karlina, 2022;Ramli et al, 2022). The development of a tourist village also requires well-planned marketing so that the activities carried out can match the needs with the offer so that buyers (tourists) and sellers (agents, institutions, companies, communities, and others in the tourism business) benefit.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The quality of this infrastructure provides good accessibility for tourists. This has a positive and significant effect on tourist satisfaction [44].…”
Section: Tourist Accessibility To and Satisfaction With Cultural-hist...mentioning
confidence: 94%